Comparison of the iLUX and the LipiFlow for the Treatment of Meibomian Gland Dysfunction and Symptoms: A Randomized Clinical Trial - Tauber J (Dove Medical Press, 2020)
Joseph Tauber,1 James Owen,2 Marc Bloomenstein,3 John Hovanesian,4 Mark A Bullimore5 1Tauber Eye Center, Kansas City, MO 64111, USA; 2TLC Laser Eye Centers-La Jolla, La Jolla, CA 92122, USA; 3Schwartz Laser Eye Center, Scottsdale, AZ 85260, USA; 4Harvard Eye Associates, Laguna Hills, CA 92653, USA; 5University of Houston, College of Optometry, Houston, TX 77204, USACorrespondence: Joseph TauberTauber Eye Center, 4400 Broadway, Suite 202, Kansas City, MO 64111, USATel +1 816 531 9100Fax +1 816 531 9105Email jt@taubereye.comPurpose: To compare the effects of eyelid treatment with the iLUX MGD Treatment System and the LipiFlow Thermal Pulsation System on objective and subjective parameters of meibomian gland function and symptoms.Patients and Methods: In this randomized, open-label, controlled, multicenter clinical trial, both eyes of 142 patients aged ≥ 18 years with Ocular Surface Disease Index (OSDI) scores ≥ 23, total meibomian gland scores (MGS) ≤ 12 in the lower eyelid of each eye, and tear break-up time (TBUT) < 10 s were randomized 1:1 to iLUX or LipiFlow treatment, with stratification by test center. The primary effectiveness endpoints were changes in total MGS (masked) and TBUT from baseline to 4 weeks. The secondary effectiveness endpoint was changed in OSDI score from baseline to 4 weeks.Results: Both devices significantly improved effectiveness outcomes, with no differences between the two devices. At the 4-week visit, mean MGS, TBUT, and OSDI scores improved at least 16.9 ± 11.5, 2.6 ± 3.2 s, and 28.0 ± 22.8, respectively, across treatment groups and treated eyes. Four device/procedure-related events occurred in the iLUX group, compared with none in the LipiFlow group, but there were no device-related adverse events that involved changes in lid margins, eyelids, or lash integrity. Corneal staining, intraocular pressure, and visual acuity did not differ in the two groups.Conclusion: Both treatments produced significant improvements in meibomian gland function and symptoms. For all effectiveness measures, there were no statistically significant differences between the two treatments.Keywords: meibomian gland dysfunction, meibomian gland score, tear break-up time, ocular surface disease index